The Ubiquitous Healthcare Facility Framework: A Proposed System for Managing Rural Antenatal Care - Maria Saleemi (IEEE Access, 2019)
Ubiquitous computing is playing a vital role in the provision of healthcare services through advanced technologies. The ubiquitous environment where resources can be accessed by anyone at anytime regardless of location have brought revolution in delivery and accessibility of healthcare services even in remote areas. Therefore, in recent years more research contributions can be seen to propose digitalized healthcare services in the form of mobile and e-Services that are accessible through ubiquitous devices. To exploit the underlining potential of ubiquitous computing, in this research we have proposed a ubiquitous healthcare framework for provision of healthcare services in remote rural areas in province of Punjab, Pakistan. The research has employed a case study research approach to understand the phenomena in depth and in its real context. The unit of analysis is provision of antenatal and child healthcare services at basic health units in the selected region. The case study is constructed through field study by engaging healthcare professionals working at basic health units and data is collected through focus group interviews with healthcare professionals. A proof-of-the-concept ubiquitous framework is proposed as part of the case study by constructing various services to facilitate healthcare professionals in rural areas. To evaluate the proposed ubiquitous framework, an evaluation framework based on usability, information system and ISO models is constructed. Hypothesis are constructed to measure user satisfaction through twelve constructs of the evaluation framework that include availability, adaptability, memorability, effectiveness, responsiveness, cognitive load, error recovery, ease to understand, ease of learning, efficiency of use, navigation, and execution. The data is collected through field surveys by conducting walkthroughs with healthcare professionals in rural areas. The analysis of the data is carried out by employing structured equation modeling in SPSS. The results provide highly significant relationship between constructs and user satisfaction. The study findings show that the healthcare problem in rural areas could be addressed through ubiquitous solutions however, while designing, constructing and evaluating these solutions, the involvement of relevant community is crucial.